Study on roof deformation and control of roof cutting without coal pillar reuse retaining roadway - Jie ZHANG; Jianping SUN; Yifeng HE; Shoushi GAO; Tong LI (Meikuang Anquan)
In order to study the deformation law of roadway roof in the reuse retaining roadway stage of “110” construction method and determine the reasonable roadway support load, and to solve the safety hazards of the reuse of the retained roadway, taking the return airway of 214202 working face of Hanjiawan Coal Mine as the research background, the mechanical structure model of the short-arm beam of the roof cutting in the reuse of the retained roadway was established, and the numerical simulation and field measurement were used to study the roof deformation law of the advance section of the roadway and the mining influence zoning when the retained roadway was disturbed by the secondary mining. The research shows that during the reuse of the return airway, the roof support strength required for the advance influence area is 12 152.98 kN. Based on the theoretical calculation, the proposed advance reinforcement support scheme can rednce the deformation of roadway roof to 118-134 mm after reinforcement, which is 58% lower than that before reinforcement; the advance influence area of the working face can be divided into four areas.